A plant-derived biostimulant Aminolom Enzimatico® application stimulates chlorophyll content, electrolyte leakage, stomata density and root yield of radishes under salinity stress - Gamze Kaya (PeerJ)
Biostimulants stimulate plant growth and tolerance to salinity stress, which creates unfavorable conditions for plant growth from emergence to harvest; however, little is known about their roles in triggering salt tolerance. Therefore, the study aimed to determine how applying a foliar plant-derived biostimulant (Aminolom Enzimatico® 24%) affects the growth (leaf area, biomass weight, root diameter, root fresh weight, and water-soluble dry matter), physiology (chlorophyll content, electrolyte leakage, cell membrane stability, and relative water content), and stomata of the lower and upper parts of leaves in radish plants (Raphanus sativus L.) under salinity stress. Radish plantlets at 7 d old were irrigated with saline water (i.e., 50, 100, 150, and 200 mM NaCl), and the biostimulant was sprayed twice at 7 d intervals. Under salinity stress, increased water-soluble dry matter content was detected, along with reduced plant biomass weight, root fresh weight, and root diameter. Meanwhile, the foliar biostimulant increased the mean root fresh weight, biomass fresh weight, and leaf area by 12%, 13.6%, and 24% compared to the control, respectively. Increasing NaCl dramatically reduced leaf area and relative water content, whereas chlorophyll content and stomata densities on both sides of the leaves improved. By regulating physiological parameters and thereby promoting root and leaf growth, the biostimulant application improved the radish plants’ tolerance to salinity stress up to 100 mM NaCl. Spraying the biostimulant can also boost plant growth, root yield, and radish quality under moderate salinity stress.